Decriminalizing Homosexuality in India and Sri Lanka: A Comparative Analysis - Nirogini, V. (Faculty of Arts University of Jaffna, Sri Lanka, 2022)
Should homosexuality be recognized as acceptable in society? The answer hinges on the debate between public morality and constitutional morality. Sexual orientation is a determining aspect of a person’s identity. It is also a matter of a person’s individuality, privacy, and dignity. Above all, it is part of the right to life, and without it, other rights cannot be enjoyed by ‘non-heteronormative’ persons. Homosexuality as a sexual orientation is about one’s sexual autonomy as well. Everyone should be treated equally as human beings irrespective of sexual orientation. However, most people disapprove of homosexuality as it is seen as practice that goes against public morality, tradition, and culture. This precisely points to the debate between the rights of the majority and the rights of the minority. The Supreme Court of India has declared that Section 377 of the Penal Code, which criminalizes consensual homosexuality amongst adults, is unconstitutional. Similarly, in Sri Lanka too, there is an identical provision which criminalizes homosexuality. A principled commitment is required to legalize homosexuality in order to address the issue of the rights of those who are marginalized/minoritized based on sexual orientation. In this context, this paper analyses the possibility of legalizing consensual homosexuality amongst adults in Sri Lanka with a comparative analysis of the legal framework relating to homosexuality in India.
Keywords: Homosexuality; Sexual minorities; Fundamental rights; Public morality; Constitutional morality